(untitled) (Research, Society and Development, 2022)
The present study aimed at the association between polypharmacy and adherence to treatment in patients with Diabetes Mellitus. It constitutes an integrative literature review. The integrative review was carried out in six stages: 1) Identification of the theme and selection of the research’s guiding question; 2) Establishment of criteria for inclusion and exclusion of studies and search in the literature; 3) Definition of the information to be extracted from the selected studies; 4) Categorization of studies; 5) Evaluation of studies included in the integrative review and interpretation and 6) Presentation of the review. It was concluded, therefore, that polypharmacy is one of the consequences of the treatment of Diabetes Mellitus, and that, in most cases, this practice is essential for good control and treatment of this morbidity. On the other hand, with regard to adherence, the need for patient education regarding medication, professional involvement and respect for the beliefs of patients with this disease are shown. Therefore, it is essential that there are more studies and data collection that address this theme, since the selected ones presented limitations, with no relationship between polypharmacy, treatment and adherence explicitly pointed out.